RELATIONSHIPS BETWEEN PERCEPTIONS, PROBLEMS AND SOLUTIONS RELATED TO THE SHOPHOUSE PHENOMENON IN BANDA ACEH CITY - Rahmi, Marlisa; Saputra, Zulhadi; Irfandi; Saputra, T. Murdani; Kusuma, Hanson E. (Rumoh Journal of Architecture, 2023)
The growth of shophouses in Banda Aceh City tends to be fast. This phenomenon cannot be separated from the consequences of Banda Aceh being a provincial capital. However, the uncontrolled growth of shophouses tends to have negative impacts on the urban environment. Therefore, this study was aimed at gaining new knowledge on perceptions held, problems encountered and solutions expected by residents related to shophouses in Banda Aceh City. This research was conducted in two stages. In the first stage, a qualitative research method was used. Data were collected using a survey with open-ended questions and analyzed using a content analysis method (text data). In the second stage, a quantitative research method was used. Data were collected using a survey with closed-ended questions and analyzed using a quantitative analysis method. Both data collection methods were executed based on online surveys. The results showed three dimensions of the perceptions of residents related to shophouses in Banda Aceh City, i.e.: Lack of Regulation, Development Consequence, and Efficiency Effort. They also showed four dimensions of the problems encountered by residents, i.e.: Environment Disturbance, Circulation Disturbance, Reduced Comfort, and Reduced Esthetic. Related to the solutions expected by residents, there were two dimensions, i.e.: Regulation Rearrangement and Public Facility Management. The results also revealed a strong relationship between the Lack of Regulation perception dimension and the Circulation Disturbance problem dimension and the Regulation Rearrangement solution dimension.